Constraints on the impactor flux to the Earth–Moon system from oxygen isotopes of the lunar regolith - Anthony M. Gargano; Justin I. Simon; Erick Cano; Karen Ziegler; Charles K. Shearer; James M. D. Day; Zachary Sharp (Proceedings of the National Academy of Sciences, 2026)
The impactor flux record to Earth has largely been erased by active tectonics, weathering, and continual reworking of the crust. Instead, a record of highly siderophile elements (HSE: Re, Os, Ir, Ru, Rh, Pt, Pd, and Au) in lunar impactites has been used as a proxy for the type of impactor material added to the Earth–Moon system. Quantifying impactor mass and flux with the HSE can potentially be complicated by numerous secondary processes, however, including silicate–metal segregation and multiple impact heritage. In contrast, because oxygen has an invariant geochemical affinity, triple oxygen isotope compositions have the potential to offer a robust long-term record of impactor fluxes in complex mixtures such as regolith. Here, we use high-precision triple oxygen isotopes to deconvolve the influences of meteorite addition and silicate vaporization and identify a ubiquitous impactor contaminant comprised of partially evaporated CM or ureilite-like material representing at least 1 wt% of the lunar regolith. Water delivered to Earth by meteorite material over 4 billion years therefore is only a fraction of an ocean’s worth of water but is a significant contributor to the ice reservoir of the lunar cold traps.